2011
DOI: 10.1111/j.1460-9568.2011.07836.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p53 and p27 Kip1 in the regulation of neurogenesis in the murine adult subventricular zone

Abstract: The tumor suppressor protein p53 (Trp53) and the cell cycle inhibitor p27 Kip1 (Cdknb1) have both been implicated in regulating proliferation of adult subventricular zone (aSVZ) cells. We previously reported that genetic ablation of Trp53 (Trp53 −/−) or Cdknb1 (p27 Kip1−/−) increased proliferation of cells in the aSVZ, but differentially affected the number of adult born neuroblasts. We therefore hypothesized that these molecules might play non-redundant roles. To test this hypothesis we generated mice lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…Indeed, we measured the level of p53 and p21 proteins after AICAR treatment, but unfortunately, very weak bands were detected in both C17.2 and primary NSCs, consistent with a previous report that p21 and p27 are not enriched in NSCs (31). It was also reported that under physiological conditions, the level of p53 detected in the subventricular zone was very low (49). All of these conclusions are consistent with the rapid proliferation and self-renewal properties of NSCs.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, we measured the level of p53 and p21 proteins after AICAR treatment, but unfortunately, very weak bands were detected in both C17.2 and primary NSCs, consistent with a previous report that p21 and p27 are not enriched in NSCs (31). It was also reported that under physiological conditions, the level of p53 detected in the subventricular zone was very low (49). All of these conclusions are consistent with the rapid proliferation and self-renewal properties of NSCs.…”
Section: Discussionsupporting
confidence: 76%
“…By contrast, the expression of the cell cycle inhibitor, Btg1 , was not affected by the loss of Chd7 (Fig. G) . We also observed a significant increase in the expression of Mtor , a key regulator of adult NSC quiescence and proliferation , in the Chd7null DG (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…The link between Brg1 and p53/p21 in regulating stem cells is plausible, as loss of p21 reduces the quiescence and accelerates the exhaustion of aNSC proliferative capacity . Moreover, loss of p53 in aNSCs leads to increased proliferation and dramatically reduced levels of p21 , while increased p53 activity reduces proliferation . Since our results show that Brg1 deletion increases p53 protein and p21 expression in neurospheres, we speculate that iBrg1 stem cells in vivo have increased cell quiescence.…”
Section: Discussionmentioning
confidence: 62%